Strengthening student communication through pediatric simulated patient encounters - Ryan Whitt; Gregory Toussaint; S. Bruce Binder; Nicole J. Borges (Journal of Educational Evaluation for Health Professions, 2014)
As medical students enter the role of physician, clinical outcomes not only rely on their mastery of clinical knowledge, but also on the effectiveness in which they can communicate with patients and family members. While students typically have numerous opportunities to practice clinical communication with adult patients, such practice in pediatric settings is limited. This study examines if simulated patient (SP) encounters strengthen third-year medical students’ communication skills during the pediatrics clerkship. During 2011-2013, three SP encounters (comprising 3 pediatric scenarios) were incorporated into a pediatrics clerkship at one United States medical school to give students a safe venue to practice advanced communication with observation and direct feedback. Third-year medical students engaged in the scenarios and received both written and oral feedback from an evaluator observing the encounter. With IRB approval, students’ self-perceived confidence and abilities at performing the advanced communication skills were measured using an eightitem, Likert scale questionnaire administered pre and post the SP encounter. Pre- and post-questionnaires (n=215; response rate, 96%) analyzed using a Wilcoxon-matched pairs signed-rank test demonstrated statistically significant increases in students’ perception of their confidence and abilities regarding their performance (P<0.05; Bonferroni correction, P<0.006). There was an increases in student confidence and self-perceived ability in: first, communicating with children and family members of young patients; second, managing confrontational situations involving parents; third, performing a thorough psychosocial history with an adolescent; and fourth, using Evidence Based Medicine to motivate parents.